Stuck at a Crossroads? The Duration of the Italian School-To-Work Transition - Francesco Pastore; Claudio Quintano; Antonella Rocca (Institute of Labor Economics (IZA), 2020)
There is a long period from completing studies to finding a permanent or temporary (but at least satisfactory) job in all European countries, especially in Mediterranean countries, including Italy. This paper aims to study the determinants of this duration and measure them, for the first time in a systematic way, in the case of Italy. This paper provides several measures of duration, including education level and other criteria. Furthermore, it attempts to identify the main determinants of the long Italian transition, both at a macroeconomic and an individual level. It tests for omitted heterogeneity of those who are stuck at this important crossroads in their life within the context of parametric survival models. The average duration of the school-to-work transition for young people aged 18–34 years was 2.88 years (or 34.56 months) in 2017. A shorter duration was found for the highly educated; they found a job on average 46 months earlier than those with compulsory education. At a macroeconomic level, the duration over the years 2004–2017 was inversely related to spending in the labour market policy and in education, GDP growth, and the degree of trade-union density; however, it was directly related to the proportion of temporary contracts. At the individual level, being a woman, a migrant, or living in a densely populated area in the South are the risk factors for remaining stuck in the transition. After correcting for omitted heterogeneity, there is clear evidence of positive duration dependence. Positive duration dependence suggests that focusing on education and labour policy, rather than labour flexibility, is the best way to smooth the transition. This study develops our understanding of the Italian STWT regime by providing new and detailed evidence of its duration and by studying its determinants.
Keywords: H52; I2; I24; J13; J24; 330; school-to-work transition; passive and active labour policy; survival models; positive duration dependence; Italy